Allosteric modulators restore orthosteric agonist binding to mutated CB(1) receptors - Dopart, Rachel (J Pharm Pharmacol, 2019)
OBJECTIVES: To determine if diminished orthosteric agonist binding due to mutations in extracellular loops 1 or 2 of the cannabinoid receptor 1 (CB(1)) can be overcome by an allosteric modulator and restore agonist binding. METHODS: Binding assays were performed using a range of concentrations of orthosteric compound, in the presence or absence of a set concentration of the allosteric modulator PSNCBAM-1 to determine the EC(50) in its absence or presence. KEY FINDINGS: Single mutations in extracellular loop 1 or 2 of CB(1) showed weak or no binding of agonist CP55940 to the receptor. Interestingly, upon addition of the allosteric modulator PSNCBAM-1, this binding was restored typically to wild-type CB(1) levels. In a few cases, the allosteric modulator ORG27569 was compared with PSNCBAM-1 for CP55940 binding and it also restored binding. Further, wild-type levels of inverse agonist bound the CB(1) mutants in the absence of modulator, suggesting the mutants were originally folded like the wild type. CONCLUSIONS: Based on our findings, we provide evidence of a therapeutic application for allosteric modulators in situations where a mutation in the receptor may hinder its function. By utilizing allosteric modulators, restoration of orthosteric binding may be possible.